Independence and legitimacy in the institutional system of the European Union - Ritleng, Dominique (Oxford : Oxford University Press, 2016)
With many EU non-majoritarian bodies growing in political influence, this volume sheds light on the inherent tension between independence and legitimacy in the EU's institutional system, and explores ways to reconcile the two.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 17, 2016).
Keywords: European Union; Legitimacy of governments; Autonomy; Law; International law